Adolescent Light Cigarette Smoking Patterns and Adult Cigarette Smoking - ConstanceWiener, R. (Adv Epidemiol, 2016)
PURPOSE: Light cigarette smoking has had limited research. The purpose of this study was to examine the relationship between light smoking in adolescence with smoking in adulthood. METHODS: National Longitudinal Study of Adolescent Health data, Waves I and IV, were analyzed. Previous month adolescent smoking of 1–5 cigarettes/day (cpd) (light smoking); 6–16 cpd (average smoking); 17 or more cpd (heavy smoking); and nonsmoking were compared with the outcome of adult smoking. RESULTS: At baseline, 15.9% of adolescents were light smokers, 6.8% were average smokers, and 3.6% were heavy smokers. The smoking patterns were significantly related to adult smoking. In logistic regression analyses, adolescent light smokers had an adjusted odds ratio (AOR) of 2.45 (95% CI: 2.00, 3.00) of adult smoking; adolescent average or heavy smokers had AOR of 5.57 (95% CI: 4.17, 7.43) and 5.23 (95% CI: 3.29, 8.31), respectively. CONCLUSION: Individuals who initiate light cigarette smoking during adolescence are more likely to smoke as young adults. PRACTICAL IMPLICATIONS: When screening for tobacco use by adolescents, there is a need to verify that the adolescents understand that light smoking constitutes smoking. There is a need for healthcare providers to initiate interventions for adolescent light smoking.